DEGRADATION OF DIMETHOATE AND PYRETHROID BY USING FUNGAL STRAINS ISOLATED FROM THE RHIZOSPHERE OF JUGLANS REGIA L. IN THE NORTHERN REGION OF JAMMU AND KASHMIR, INDIA - MANSOOR AHMAD LONE,; MOHD. RAFIQ WANI, (International Journal of Pharma and Bio Sciences, 2012)
Indiscriminate use of chemicals regardless of climate, soil vigor and other factors has adversely affected the environmental quality and soil ecosystem. Fungi play a key role in maintaining the biogeochemical cycles in the soil by utilizing many recalcitrant chemical compounds and some common insecticides. In the present study, many fungal species were isolated from the rhizosphere of Juglans regia L. in the Northern regions of Jammu and Kashmir, India and tested in this insecticide utilization-screening programme. Among the isolated strains, only Trichoderma koningii, Penicillium notatum, Aspergillus terricola and A. niger were successful in degrading the supplemented insecticides viz., dimethoate and pyrethroid. The strains exhibited the optimal growth in the temperature range of 20-300C. The two insecticides were provided as the sole source of carbon and nitrogen in the Potato Dextrose Agar (Hi Media). Trichoderma koningii used dimethoate as carbon source at a faster rate compared to that of pyrethroid as the nitrogen source. However, Penicillium notatum and Aspergillus niger used dimethoate both as carbon and nitrogen sources. Trichoderma koningii and Aspergillus niger utilized pyrethroid as carbon source more vigorously than Penicillium notatum and Aspergillus terricola.